Rancang Bangun Sliding Cutting Jig Guna Mengoptimalkan Fungsi Kerja Mesin Gerinda Tangan Sebagai Alat Potong Plat Lembaran - Eko Slamet Riyadi; Erlina Kusumawati (Jurnal Pengelolaan Laboratorium Pendidikan, 2022)
The process of cutting sheet steel plates is a mandatory work that must be done in a manufacturing process that uses plate-based materials. Cutting of sheet steel plates is usually done using a shearing machine, a cutting grinding machine, plate scissors and weld cutting. The purpose of this study focuses on improving the performance capability of the machine / tool, especially in hand grinding machines so that their function is not only limited to cutting workpieces under the hand, but its function can be maximized to cut sheet plates, box pipes, hollows more easily and quickly by adding jig components as supporting components. The stages that must be done are including design, cutting materials in accordance with the design plan, parakitan (Asembly), finishing, the next stage is testing the working ability of the tool. As for the manufacturing site, testing of the working method of the tool is carried out in the laboratory of bench work and plate majoring in mechanical engineering of Banyuwangi State Polytechnic. From the test results, the plate cutting time using a sliding cutting jig tool becomes faster at approximately 2 -3 minutes than a grinder without being installed on the aid tool. From the results of research that has been done, it is seen that the function of tool performance from hand grinding becomes more optimal and able to contribute to the lecture practicum of bench and plate work in the laboratory of bench and plate work department of Mechanical Engineering Banyuwangi State Polytechnic.